A comparative study of the method of Williamson Hall and the pattern of cadmium oxide nanoparticles for X-rays - Mohammed, Esraa Ahmed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
X-ray difraction (XRD) is an effective non-destructive instrument used in the determination and analysis of amorphous and crystalline materials. Three basic elements are the X-ray diffractometers: the X-ray tube, a retention of samples and an X-ray detector. In many industries such as diodes, transistors, detectors, solar and photovoltaic cells, cadmium oxide CdO nanoparticles are used. For this analysis, CdO nanoparticles are semi-conductors (type) and band-gaps of 2.5 eV and 1.98 eV in direct and indirect bands using cadmium oxide. Several temperatures, effects and parameters such as texture coefficient (TC), dislocation density(μ), special area (SSA), and micro strain were measured and determined (S). The peaks of the analysis were the extension of the nano structure, crystal size and grid pressure of the CdO and were measured using the Size Train Plot of Williamson-Hall (SSP). The composition of the particle is the cubic fluorite and spatial group Fm-3m (225). In the peaks resulting from the calcination process, strain enlargement was observed. Accordingly, the above procedure determined all physical parameters as a result of the diffraction effects.